PENINGKATAN HASIL BERFIKIR KRITIS SISWA MATERI SISTEM PENCERNAAN MAKANAN MENGGUNAKAN MEDIA VIDIO PEMBELAJARAN PADA KELAS XI IPA SMA NEGERI 09 MATARAM - Aditya Pratama; Yen Kusnita; I Wayan Merta (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2023)
The purpose of this study was to determine increasing critical thinking skills of class XI MIA 1 SMA Negeri 9 Mataram students on digestive system material using learning video media. The research method used is Classroom Action Research (PTK) which generally consists of two cycles. Each cycle has the same stage that is planning, action, observation, and reflection. This research is related to food digestive system material and was carried out in class XI MIA 1 SMA Negeri 9 Mataram with a total of 30 students.. The data collection techniques used were observation sheets, documentation and critical thinking instruments. The research results showed that the percentage of students who met the standards in cycle II was 100%. The improvement in the results of students' critical thinking abilities in the human food digestive system material has been completed with a completion percentage of 100% so it is proven that learning video media can improve students' critical thinking abilities and influence learning outcomes.